ANALISIS KONTRIBUSI PAJAK HOTEL TERHADAP PENDAPATAN ASLI DAERAH DI KABUPATEN BERAU: ANALISIS KONTRIBUSI PAJAK HOTEL TERHADAP PENDAPATAN ASLI DAERAH DI KABUPATEN BERAU - Hajran Jamilah (ECO-BUILD, 2020)
The aim of this study was to find out how far the Contrbution of Hotel Tax to Own Source Revenue of Berau District in 2013 – 2018. The data used in this study is the quantitave data taken from the institutions related to this studi such as Central Bureau of Statistics and Local Government Finance and Management Office of Berau District. The methodology used in this study is library research and secondary data obtained from book, scientific journal, and the previous study. The instrument used by the researcher is the formula to find out the contribution, then it confirmed to the table of classification criteria. The result of this study concluded that the contribution of Hotel Tax to Own Source Revenue of Berau District tend to increase year by year. However, based on the average calculation, the contribution is about 1,65% or determined as “less contribution” which means the hypothesis in this study is rejected.